Fragility in the elderly participants of coexistence and health promotion groups in the aging - Filho, Bartolomeu Fagundes de Lima; Dantas, Diego de Sousa; Sá, Fernanda Diniz de; Oliveira, Luciane Paula Batista Araújo de (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
INTRODUCTION: The frailty syndrome is a complex condition that permeates the life of the elderly, with the decrease of the homeostatic reserve of the organism and loss of resistance to the stressors, caused as results of many factors, but mainly by sarcopenia. Such syndrome makes the elderly vulnerable to illness and may lead to terminal stages of life if there is no adequate treatment. OBJECTIVE: To evaluate the influence of the factors related to the frailty phenotype in the occurrence of this in participants of groups of coexistence and health promotion of the city of Santa Cruz/RN. METHOD: This is a descriptive, associative and transversal of quantitative approach study with 60 elderly. The socioeconomic condition and the fragility phenotype was evaluated. RESULTS: the mean age of the sample was 66.1 years (SD=5.08). Most of them (53.3%) are in the age group of 60-69 years, does not have a partner (63.4%) and are illiterate (58.3%). In the mentioned morbidity, 42 (70%) reported some morbidity and hypertension was more prevalent in the sample (53.3%), followed by diabetes (20%) and osteoporosis (18.3%). Four elderly were fragile, forty-nine were pre-fragile and seven were non-fragile. There was a significant correlation in unintentional loss of weight (0.017), exhaustion (<0.001) and slowness in gait (<0.001) in the occurrence of pre-frailty. CONCLUSION: the prevalence of pre-frailty indicators in the investigated groups indicates warning signs so that actions more strongly linked to the prevention of this aggravation become a priority in the planning of the undertaken interventions in groups. Participation in social groups has a protective effect in the prevention of frailty in the elderly.